Comparative Synagogue Architecture in the Venetian Ghetto, 1500-1800. - Cannon, Emily W. (Tufts Archival Research Center, 2014)
Abstract: A comparative analysis of the five original synagogues in the Venetian Ghetto from their construction in the 1500s through their renovations in the 1700s. In addition to comparison within the synagogues there is also an in-depth look at the synagogues and how they relate to other synagogues in Europe and churches within Venice.